Hubungan Perilaku Aspek Bullying dengan Tingkat Harga Diri pada Anak Usia Sekolah Dasar Negeri 11 Banda Aceh (Lembaga Pengembangan Kinerja Dosen, 2025)
Bullying is an aggressive act that is often repeated and directed at individuals in a weaker position, causing detrimental effects on psychological aspects, particularly children's self-esteem. When children's self-esteem is low, they tend to consider themselves worthless and choose to avoid social interaction. This study aims to analyze the correlation between Bullying behavior and self-esteem levels among elementary school students. The research was conducted using a quantitative approach with a cross-sectional design. All 97 students in grades IV, V, and VI at SD Negeri 11 Banda Aceh were used as research subjects through total sampling. The questionnaire used included indicators of Bullying behavior and self-esteem levels. Based on the data obtained, of the 54 students identified as experiencing high levels of Bullying behavior, 44 children or 45.4% showed low self-esteem. On the other hand, of the 43 students who were exposed to low levels of Bullying, 35 of them, or about 36.1%, had high self-esteem. The chi-square test in this study produced a p-value of 0.000, indicating a significant relationship between Bullying patterns and self-esteem levels in children. Thus, it can be concluded that an increase in Bullying experiences in the school environment has an impact on the decline in students' self-esteem.